Pengembangan Modul Pembelajaran Instalasi Penerangan Listrik di Sekolah Menengah Kejuruan - Khoirul Huda Batubara; Hambali Hambali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
The module is one of the tools used by educators which aims to deliver learning material so that it is easier to learn independently. The background of this research is that the learning process in schools has not been implemented properly, due to the lack of a complete level of use of learning media that is easy for students to understand so that the level of student understanding has not been fulfilled and students have not been able to learn independently. This study aims to produce a valid and practical electric lighting installation learning module at SMK Negeri 2 Padangsidimpuan. This research uses the development research (R&D) method with a model adapted into 4-P consisting of Definition, Design, Development, and Deployment. The subjects of this study were students of class XI TITL at SMK Negeri 2 Padangsidimpuan. Analysis based on research obtained media validation with valid categories and material validation obtained with valid categories. The results of the Practicality test with educator respondents getting results in a very practical category and respondents from class XI TITL SMK Negeri 2 Padangsidimpuan stated that the electric lighting installation learning module was in a very practical category. Thus the electric lighting installation learning module is valid and practical and can be used in the learning process.